Hypo-activation in the executive core of the sustained attention network in adolescent offspring of schizophrenia patients mediated by premorbid functional deficits - Diwadkar, Vaibhav A.; Segel, Jamie; Pruitt, Patrick; Murphy, Eric R.; Keshavan, Matcheri S.; Radwan, Jacqueline; Rajan, Usha; Zajac-Benitez, Caroline (Psychiatry research. Neuroimaging, 2011)
Adolescent offspring of schizophrenia patients (SCZ-Off) are vulnerable to psychiatric disorders. Assessing relationships between clinical and biological measures (such as functional magnetic resonance imaging, fMRI) may elucidate pathways of vulnerability in this group. Here we assessed the relationship between clinically assessed premorbid function, and cortico-striatal activity during sustained attention in controls (HC: with no family history of psychosis) and SCZ-Off. Subjects ( n = 39) were assessed using the Structured Interview for Prodromal Syndromes and the Scale of Prodromal Symptoms. Based on the Global Assessment of Functioning (GAF) score, SCZ-Off were cleaved into "high" or “low” clinically functioning sub-groups (SCZ-Off HF, SCZ-Off LF respectively). During fMRI, subjects participated in a modified continuous performance task (CPT-IP). fMRI was conducted on a Bruker MedSpec 4 T system (345 EPI scans; TR = 2 s; 24 slices; 3.8 × 3.8 × 4 mm). Results show SCZ-Off LF evinced less activation than both HC and SCZ-Off HF in the executive core of the brain's attentional system (anterior cingulate, dorsal prefrontal cortex and caudate), but not visuo-spatial regions such as primary visual or superior parietal cortex. Differences were independent of behavioral performance, and reduction in activity was related to GAF score in a dose-dependent manner. Assessing the relationship between clinical measures and brain activity in domains such as attention provides a window into mechanisms of vulnerability in the developing adolescent brain.